Assessing institutional readiness for implementing the National Language Policy Framework for public higher education institutions in South Africa - Ravyse, N.; van Dyk, T.; Wilkin, I.; du Plessis, D. (South African Journal of Higher Education, 2026)
This article investigates the institutional readiness of South African public higher education institutions for the implementation of multilingual language policies, specifically focusing on the recently promulgated National Language Policy Framework for Public Higher Education Institutions (NLPFPHE). Drawing on applied linguistics, Weiner’s (2009) theory of organisational readiness for change, and policy implementation studies, the authors explore how various institutional factors shape the capacity to implement language policies effectively. Using a mixed-methods approach, data from the national language audit (Van Dyk, Wilken, Ravyse, Du Plessis, Khumalo and Steyn, 2023) to assess current preparedness is analysed. The findings highlight key areas where institutions demonstrate readiness, such as staff engagement with policy, but also expose critical gaps in resources and student awareness. Moreover, the authors advocate for applying organisational readiness theory as a framework for guiding language policy implementation without specific models from the Department of Higher Education and Training (DHET). By outlining challenges and opportunities in the current landscape, this article offers practical insights for institutions that foster linguistic inclusivity and excellence. It aims to empower stakeholders with a structured approach to assess readiness, address gaps, and enhance the implementation of multilingual language policies.